Overweight or Obesity: Serum Lipids in a University Population of Barranquilla Colombia (2021)
Introduction: According to the World Health Organization, overweight and obesity occur due to an abnormal or excessive accumulation of body fat that is harmful to health. During childhood and adolescence, risk factors such as dyslipidemia or obesity are detected, the maintenance of which in the adult stage has been verified, indicating that detection should be started as early as possible. It is necessary to carry out an anthropometric <- nutritional evaluation to detect a deficit or excess weight in time. A study on the topic of chronic non-communicable diseases in Colombia indicated that in 2014 more than 100,000 people died with ischemic and hemorrhagic cerebrovascular diseases (CVDs), cancer, DM and chronic obstructive pulmonary disease (COPD), by being able to carry out early detections that will allow adequate prevention of secondary complications. Methodology: An observational, descriptive, cross-sectional study was carried out with a population - sample of 36 university students of both sexes. After informed consent, those who met the inclusion criteria demanded by Bioimpedance included: weight, height, visceral fat, body fat, In addition to abdominal or waist circumference, hip and lipid profile: total cholesterol (CT), triglycerides (TG), HDLc, VLDLc. LDLc. Results: Overweight and obesity in the results of (BMI, Gf and FV)), found in young male and female sex with prevalence in the male sex group, and hyperlipidemias mainly in the female sex studied. Conclusion: High prevalence of CVD risk factors such as overweight, obesity, and hyperlipidemia in the female sex group.